Pinocembrin Decreases Atrial Fibrillation Susceptibility in a Rodent Model of Depression - Ran, Qian; Chen, Xiaoli; Zhang, Cui; Wan, Weiguo; Ye, Tianxin; Sun, Yazhou; Zhao, Xin; Shi, Shaobo; Yang, Bo; Zhao, Qingyan (Frontiers in Cardiovascular Medicine, 2022)
Background Depression is often comorbid with cardiovascular diseases and contributes to the development and maintenance of atrial fibrillation (AF). Ample research demonstrated that pinocembrin had protective effects on the neuropsychiatric and cardiovascular systems via its pharmacological properties. However, whether pinocembrin protects from AF in depression models is not known. The present research investigated antiarrhythmic effects of pinocembrin and the underlying mechanisms in depressed rats. Methods One hundred and ten male Sprague Dawley rats were randomly divided into six groups: the CTL group (the normal rats administered saline), the CTP group (the normal rats administered pinocembrin), the MDD group (the depressed rats administered saline), the MDP group (the depressed rats administered pinocembrin), the MDA group (the depressed rats administered apocynin), and the MPA group (the depressed rats administered both pinocembrin and apocynin). Chronic unpredictable mild stress (CUMS) was performed for 28 days to establish the depression model. Pinocembrin was administered via gavage from Day 8 to Day 28, and apocynin was administered via intraperitoneal injection from Day 1 to Day 28. The effects were evaluated using behavioral measurements, in vitro electrophysiological studies, whole-cell patch-clamp recordings, biochemical detection, Western blot, and histological studies. Results Pinocembrin treatment significantly attenuated the abnormality of heart rate variability (HRV), the prolongation of action potential duration (APD), the shortening of the effective refractory period (ERP), the reduction of transient outward potassium current (Ito), and the increase in L-type calcium current (ICa–L), which increase susceptibility to AF in a rat model of depression. Compared to the depressed rats, pinocembrin also increased the content of Kv4.2, Kv4.3, and atrial gap junction channel Cx40 and decreased the expression level of Cav1.2, which ameliorated oxidative stress and inhibited the ROS/p-p38MAPK pro-apoptotic pathway and the ROS/TGF-β1 pro-fibrotic pathway. Conclusion Pinocembrin is a therapeutic strategy with great promise for the treatment of AF in depressed patients by reducing oxidative stress.